Technological Innovations for Business, Education and Sustainability - Hamdan, Allam (Technological Innovation and Sustainability for Business Competitive Advantage Series, 2024)
Fulfilling a growing need for aligning business strategy and educational curriculums with the evolving skills required for business workplaces, this book presents a thorough understanding of how business, education and technology can enable current and future leaders to contribute positively to digital transformation across the globe